2019
DOI: 10.4300/jgme-d-18-00979.3
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Evidence Supporting Factors Used by Residency Program Directors to Select Applicants for Interviews

Abstract: Background Residency applicants feel increasing pressure to maximize their chances of successfully matching into the program of their choice, and are applying to more programs than ever before. Objective In this narrative review, we examined the most common and highly rated factors used to select applicants for interviews. We also examined the literature surrounding those factors to illuminate the advantages and disadvantages of using them as differentiating elements in interviewee selection. Methods Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 47 publications
2
45
0
1
Order By: Relevance
“…As many medical students now will miss out on the valuable experiences of presentations, clinical rotations, and collaborative experiences -standards which helped previous generations become future doctors -the question arises of how students will evolve and integrate themselves into the medical community. When considering the reasons why conference presentations and extracurricular activities become so central to residency applications, it is important to recall what they actually represent for each student [1]. Therefore, we must consider how medical students can develop and demonstrate skills such as knowledge, determination, and collaboration and best prepare for the careers ahead of them in the face of these recent changes.…”
Section: Editorialmentioning
confidence: 99%
“…As many medical students now will miss out on the valuable experiences of presentations, clinical rotations, and collaborative experiences -standards which helped previous generations become future doctors -the question arises of how students will evolve and integrate themselves into the medical community. When considering the reasons why conference presentations and extracurricular activities become so central to residency applications, it is important to recall what they actually represent for each student [1]. Therefore, we must consider how medical students can develop and demonstrate skills such as knowledge, determination, and collaboration and best prepare for the careers ahead of them in the face of these recent changes.…”
Section: Editorialmentioning
confidence: 99%
“…Although Step 1 of the United States Medical Licensing Examination (USMLE) is often used as a comparative factor, most studies do not demonstrate its predictive value for resident performance, except in the event of a test failure. It has also been found that structured letters of recommendation for a specialty have increased benefits when compared to generic letters (Hartman, Lefebvre, & Manthey, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The predictive ability of various application data or summative scoring rubrics on future resident performance has been mixed. 14,15,17,18 Previously used scoring rubrics may need to be restructured or reweighted, by potentially incorporating diversity as a metric to mitigate existing structural bias within medicine. Expanding screening tools to capture a broader spectrum of candidate aptitudes may help to create more diverse classes of residents.…”
Section: Revisiting Selection and Rankingmentioning
confidence: 99%